Pendampingan Dalam Meningkatkan Kualitas Baca Al Qur’an Dengan Metode Yanbu’a Di TPQ Raudlatus Salam Kencong Kepung Kediri - Nurul Fauziyah; Khoirotul Izzah (LP3M IAIFA Kediri, 2021)
In the social environment of the community at this time it is possible that there are many problems about the weak ability to read the Qur'an, therefore it should be made aware of this and demanded to solve it. Based on this context, the PKM research program is carried out and directed to improve the quality of reading the Qur'an by using yanbu'a methods and motivate children to follow the activities of preaching in tpq without any shame or anything. The assistance activities of the PKM research program are considered quite successful in resuscitating the community about the current environmental conditions. Data collection is done by conducting interviews, observations and documentation. With the emergence of achievement cards, the children tpq become more disciplined and eager to go to preach. With the increase in discipline and spirit in learning to preach, it will increase its quality and intelligence in reading the Qur'an.